1998
DOI: 10.1074/jbc.273.32.20276
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Dinucleotide Flipping by DNA Photolyase

Abstract: DNA photolyases repair pyrimidine dimers via a reaction in which light energy drives electron donation from a catalytic chromophore, FADH ؊ , to the dimer. The crystal structure of Escherichia coli photolyase suggested that the pyrimidine dimer is flipped out of the DNA helix and into a cavity that leads from the surface of the enzyme to FADH ؊ . We have tested this model using the Saccharomyces cerevisiae Phr1 photolyase which is >50% identical to E. coli photolyase over the region comprising the DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 39 publications
5
51
0
Order By: Relevance
“…It had been hypothesized that the CPD has to be flipped out of the double helix into the active site of PL for efficient electron transfer leading to repair (6). Many results support this hypothesis (6,9,25–31). A recent crystal structure (9) showed that PL binds a flipped CPD‐substrate analog leaving the opposing adenine bases unpaired.…”
Section: Introductionmentioning
confidence: 86%
“…It had been hypothesized that the CPD has to be flipped out of the double helix into the active site of PL for efficient electron transfer leading to repair (6). Many results support this hypothesis (6,9,25–31). A recent crystal structure (9) showed that PL binds a flipped CPD‐substrate analog leaving the opposing adenine bases unpaired.…”
Section: Introductionmentioning
confidence: 86%
“…5). If thymidine dimer repair occurs, the conformation of the backbone should, on the other hand, change while the enzyme–product complex decays (or the enzyme–substrate complex is formed), because the chemical environment of the backbone phosphate is altered: In an enzyme–DNA complex, electrostatic interaction of backbone phosphate and basic residues of the DNA photolyase significantly contribute to the DNA binding of the enzyme [41–44]. Therefore, an additional difference band at 1244/1224 cm −1 can be detected in Fig.…”
Section: Enzyme‐catalysed Photorepair Of Photodamaged Dnamentioning
confidence: 99%
“…80 For instance, the T<>T repair by photolyase as well as the DNA alkylation repair by iron-containing enzymes like AlkB are all conducted under this mechanism. 8183 The phosphodiester linker in the dinucleotide SP is more likely to function as the conformational holder as that in T<>T, as reflected by the slightly decreased enzyme reaction rate using SP with a formacetal linker as the substrate 68 and the much reduced rate when the linkage is absent. 61,6364 …”
Section: Sp Repair Via Splmentioning
confidence: 99%